Annual Plan 2001-2002 Haryana State - Planning Commission (Planning Commission, 2001)
Year, 2001-2002 is the last year of the Ninth Five Year Plan 1997-2002. The Ninth Plan for the State was formulated with the total outlay of Rs. 11600 crore at current prices. This size of the Plan was approved on the basis of the assessment of Resources at that time.
Planning Department Government of Haryana